Voluntary exercise is motivated by ghrelin, possibly related to the central reward circuit. Issue 1 (January 2020) - Mifune, Hiroharu; Tajiri, Yuji; Sakai, Yusuke; Kawahara, Yukie; Hara, Kento; Sato, Takahiro; Nishi, Yoshihiro; Nishi, Akinori; Mitsuzono, Ryouichi; Kakuma, Tatsuyuki; Kojima, Masayasu
Abstract : We previously reported that voluntary exercise contributed to the amelioration of abnormal feeding behavior with a concomitant restoration of ghrelin production in a rat model of obesity, suggesting a possible relationship between exercise and appetite-regulating hormones. Ghrelin is known to be involved in the brain reward circuits via dopamine neurons related to motivational properties. We investigated the relevance of ghrelin as an initiator of voluntary exercise as well as feeding behavior. The plasma ghrelin concentration fluctuates throughout the day with its peak at the beginning of the dark period in the wild-type (WT) mice with voluntary exercise. Although predominant increases in wheel running activity were observed accordant to the peak of plasma ghrelin concentration in the WT mice, those were severely attenuated in the ghrelin-knockout (GKO) mice under either ad libitum or time-restricted feeding. A single injection of ghrelin receptor agonist brought about and reproduced a marked enhancement of wheel running activity, in contrast to no effect by the continuous administration of the same drug. Brain dopamine levels (DAs) were enhanced after food consumption in the WT mice under voluntary exercise. Although the acceleration of DAs were apparently blunted in the GKO mice, they were dramatically revived after the administration of ghrelin receptor agonist, suggesting the relevance of ghrelin in the reward circuit under voluntary exercise. These findings emphasize that the surge of ghrelin plays a crucial role in the formation of motivation for the initiation of voluntary exercise possibly related to the central dopamine system.